Determinan Belanja Pegawai Pada Pemerintah Kabupaten/Kota di Provinsi Jambi - Yowana Rachma Mutmaina (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2017)
This study aimed to analyze: 1) The allocation of personnel expenditures in the district/city in Jambi Province. 2) Factors affecting personnel expenditure in the Regency / City in Jambi Province. The data used is secondary data based on panel data. The analysis tool used is panel data regression analysis. The results of the study found that: 1) During the period 2010-2014, the development of personnel spending in districts / city in Jambi Province showed an increasing trend; 2) The number of employees has a significant negative and significant impact on the expenditure of district / municipality employees in Jambi Province, while the number of Local Government’s Agencies (SKPD) has a positive and significant impact. Key Word : Personnel Expenditure, employees dan Local Governments’ Agencies Abstrak.Penelitian ini bertujuan untuk menganalisis: 1) Alokasi belanja pegawai kabupaten/kota di Provinsi Jambi. 2) Faktor-faktor yang mempengaruhi belanja pegawai pada Kabupaten/Kota di Provinsi Jambi. Data yang digunakan adalah data sekunder berdasarkan data panel. Alat analisis yang digunakan adalah analisis regresi data panel. Hasil penelitian menemukan bahwa: 1) Selama periode 2010-2014, perkembangan belanja pegawai pada kabupaten/kota di Provinsi Jambi menunjukkan kecenderungan yang terus meningkat; 2) Jumlah pegawai berpengaruh negatif dan signifikan terhadap belanja pegawai Kabupaten/Kota di Provinsi Jambi, sedangkan jumlah SKPD berpengaruh positif dan signifikan. Kata Kunci : Belanja Pegawai, Pegawai, Satuan Kerja Perangkat Daerah